2014
DOI: 10.1371/journal.pone.0115204
|View full text |Cite
|
Sign up to set email alerts
|

Evodiamine Induces G2/M Arrest and Apoptosis via Mitochondrial and Endoplasmic Reticulum Pathways in H446 and H1688 Human Small-Cell Lung Cancer Cells

Abstract: The goal of this study was to evaluate the ability of EVO to decrease cell viability and promote cell cycle arrest and apoptosis in small cell lung cancer (SCLC) cells. Lung cancer has the highest incidence and mortality rates among all cancers. Chemotherapy is the primary treatment for SCLC; however, the drugs that are currently used for SCLC are less effective than those used for non-small cell lung cancer (NSCLC). Therefore, it is necessary to develop new drugs to treat SCLC. In this study, the effects of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 47 publications
5
37
1
Order By: Relevance
“…Its apoptosis was based on annexin V/PI analysis and reached to about 20% for annexin V positive. In contrast, several drugs were reported to G2/M arrest and apoptosis without detectable subG1 accumulation, such as erianin in human osteosarcoma cells, evodiamine in lung cancer H446 and H1688 cells, withametelin in lung cancer A549 cells, and diarylpyrazole derivative (AM251) in A375 cells . Similarly, we found that sinularin induced G2/M arrest and apoptosis without detectable subG1 accumulation in oral cancer cell at 24 h treatment, where the apoptosis was confirmed by flow cytometry (annexin V/PI and pancaspase analyses) and western blotting (caspases 3, 8, 9, and PARP).…”
Section: Discussionsupporting
confidence: 52%
“…Its apoptosis was based on annexin V/PI analysis and reached to about 20% for annexin V positive. In contrast, several drugs were reported to G2/M arrest and apoptosis without detectable subG1 accumulation, such as erianin in human osteosarcoma cells, evodiamine in lung cancer H446 and H1688 cells, withametelin in lung cancer A549 cells, and diarylpyrazole derivative (AM251) in A375 cells . Similarly, we found that sinularin induced G2/M arrest and apoptosis without detectable subG1 accumulation in oral cancer cell at 24 h treatment, where the apoptosis was confirmed by flow cytometry (annexin V/PI and pancaspase analyses) and western blotting (caspases 3, 8, 9, and PARP).…”
Section: Discussionsupporting
confidence: 52%
“…Therefore, the observation that PDGF-BB increased and evodiamine decreased the expression of p21 in the present study was not unusual. Of note, the inhibitory effects of evodiamine on cell cycle progression have been previously observed in various human tumor cell lines, including small-cell lung cancer cells (20), gastric cancer cells (11), breast cancer cells (21), gastric adenocarcinoma cells (22) and cervical carcinoma HeLa cells (23), and are considered to be important in the antitumor action of evodiamine. The data obtained in the present study extends the current recognition of evodiamine, and suggested that the regulation of cell cycle progression by evodiamine may be general and function in a broader range of cell types, including tumor cells and vascular cells.…”
Section: Discussionmentioning
confidence: 97%
“…Intracellular Ca 2+ may be also involved in mitochondrial dysfunction. Previous reports have shown that several anticancer drugs induce G2/M cell cycle arrest and apoptosis by depolarizing mitochondrial membrane potential and increasing intracellular Ca 2+ (Fang et al, 2014;Guo et al, 2014). With respect to intracellular Ca 2+ , there has been also reported that TBT induces mobilization of Ca 2+ from intracellular stores and results in phosphorylation of MAPKs because its suppression by chelation of intracellular Ca 2+ in human T lymphoblastoid cells (Yu et al, 2000).…”
Section: Discussionmentioning
confidence: 98%